Experimental analysis of the transdifferentiation of visceral to parietal endoderm in the mouse. - Ninomiya, Y; Davies, T; Gardner, R (2005)
The visceral endoderm (VE) of isolated extraembryonic regions (ExEmbs) of 7 days postcoitum (dpc) prestreak mouse conceptuses have been shown to convert readily to parietal endoderm (PE). The present study addresses the following three unanswered questions. On what does conversion depend, how rapidly does it occur, and is it an enduring general property of a residual small population of relatively immature cells? In situ hybridization reveals that change in cell state occurs within 2 days of culture. Deprivation of the mesoderm also promotes it in later ExEmbs. Conversely, the conversion to PE in isolated 7 dpc ExEmbs is suppressed by grafting 8 dpc or 9 dpc mesoderm. Hence, the conversion provides an example of transdifferentiation that is promoted by the absence of extraembryonic mesoderm. The presence of mesoderm seems to be necessary to enable the VE to grow rather than convert to PE, as occurs if it retains contact with the extraembryonic ectoderm.